Van Gölü'nün Su Bütçesi Ve Havza İklimi - Batur, Eşref (Fen Bilimleri Enstitüsü, 1996)
Dünyanın en büyük dördüncü gölü olan Van Gölü'nün su seviyesi 1987 yılından itibaren sürekli olarak yükselmeye başlamış ve 1995 yılında ortalama seviyesinin iki metre kadar üzerine çıkarak 1650 m kotunu aşmıştır. Bu durumda göl çevresindeki arazinin her türlü kullanımı artan bir şekilde engelllenmiş, özel-kamuya ait değerler kullanılamaz hale gelmiştir. Van Gölü'nün ortalama deniz seviyesinden olan yükseldiği 1646 metre iken 3502 km2'lik bir su yüzeyine sahipti. Bu su seviyesi ile göl, 576 milyar m3 su içermekteydi. Göl'ün su girdisi, 12596 km2'lik drenaj alanındaki yüzeysel akış, miktarları bilinmeyen yeraltı suyu ve direkt olarak göl üzerine düşen yağıştan oluşmaktadır. Gölden su çıktısı büyük ölçüde buharlaşma ile olmaktadır. Bu nedenle bu kapalı göldeki su hacmi, havzaya hakim iklim şartlarına karşı oldukça duyarlıdır. Bu çalışmada, ilk olarak yağış, rüzgar, bağıl nem ve sıcaklık paremetrelerinin Van Gölü Havzasındaki yersel dağılımı incelenmiş ve bu parametrelerin su seviyeleri ile ilişkileri üzerinde durulmuştur. Daha sonra, Van Gölü'nün su bütçesi çıkartılarak, Göl' deki seviye yükselmesi açıklanmaya çalışılmıştır. Yapılan incelmede su seviyesinin arttığı 1987 ve 1988 yıllarında, Göle gelen toplam girdi (yağış ve akış) artarken gölden olan buharlaşma giderek azalmış ve yağışlı geçen ardışık bu iki yıl boyunca göle gelen toplam girdi, buharlaşma ile dengelenememiş ve aradaki hacim bugünkü farkı su seviyesinde artışa neden olduğu tespit edilmiştir. Ayrıca su dengesi metodu ile hesaplanan gölden olan buharlaşma, klasik şekilde tava katsayısı kullanılarak hesaplanan göl buharlaşması ile karşılaştinlmıştir. Değişik kaynaklarda verilen su bütçe hesaplarında tava katsayısı ile Van Gölü'nden olan toplam buharlaşmanın yanlış hesaplandığı ve gölden olan gerçek buharlaşmayı kesinlikle temsil etmediği açık bir şekilde gösterilmiştir. Son bölümde ise Van Gölü'ndeki su seviye yükselmesinin tektonik hareketler ve güneş lekeleri ile ilgili olmadığı gösterilmiştir.

Between 1987 and 1994, water level of Lake Van increased about 2 meters. Lake Van is the largest soda-lake on earth. Its water is derived from the rivers in its basin and its own net basin supply consisting of precipitation, runoff, and lake evaporation. Its volume is 607 km3, which makes it the fourth largest closed lake. It comprises about 16596 km2 of lake surface and drainage basin. Its mean height from the sea level is 1646 m and it has a water surface area of 3502 km2. The amount of water coming to Lake Van, consists of surface runoff, unknown underground water and precipitation. Outgoing from the lake happens by evaporation largely. Because of that, the water volume of this closed lake depends on the climate conditions on the drainage basin (Kadıoğlu, 1995a). One of the most important hypothesis related to the water level changes on the lake is the water budget. Precipitation, inflow, outflow, evaporation, seepage are the most important parameters which affect the budget of any lake. The water budget of a closed lake is determined by total evaporation occurring over its surface. If the lake doesn't change its level, the input by direct precipitation and by river inflow must balance the evaporation (Kempe et al., 1978). The estimation of evaporation from free water surfaces is difficult due to the fact that there are many parameters which affects the event. Several methods, such as Water Balance Method, Evaporation pan, Aerodynamic formulas, Penman's Equation, Energy Balance Method, exist in order to estimate the evaporation loss from the free water surface. Some of these methods require extensive instrumentation while others are based on routine meteorological observations and standard tables (Balek et al., 1994). Penman's approach is the most widely used method for computing lakes' and reservoirs' evaporation from routine meteorological observations. To be able to use Penman's method, it is certainly necessary to know the water temperature. Due to the difficulties in measuring the parameters used in energy balance method, energy method is rarely used (Bayazat, 1991). Since automatic stations are not available on Lake Van, parameters such as the water temperature, air temperature just over the free water surface and intensity and direction of the wind above 2 m from the free water surface can not be measured. Therefore, evaporation over Lake Van can only be estimated by the classical method which consist of the application of a lake-to-pan coefficient to the observed pan evaporation at the side of the Lake. ?C-lake v> Upan {,'?) Here: Eiake = Lake evaporation (mm), Epm = Pan evaporation (mm), C = The lake to pan coefficient. Here the assumption is made that, on an annual basis, the change in energy storage of the lake and net advected energy into or out of the lake are negligible (Balek et al., 1994). However, there are important points to be attended; 1) The water in the evaporation pan at the meteorological station is fresh water, but, Lake Van is a salt-soda Lake. As is known, since the evaporation in the fresh water is 2-3 % higher than that of salty water, the evaporation at the pan does not represent the evaporation from Lake Van (Muslu, 1993). 2) The multiplication of the measured evaporation in the meteorological station by the pan coefficient means that the influence of the depth of Lake Van upon rate of evaporation is negligible. The effect of depth of the lake Van upon rate of evaporation may be quite considerable. Seasonal temperature regime of a shallow water body, e.g., a small lake, will normally approximate closely to the seasonal air temperature regime, so that maximum water temperatures are reached in the mid- to late-summer months and minimum water temperatures in the mid- to late-winter months. This means that maximum rate of evaporation from a shallow water body will be experienced during the summer, and minimum rates during the winter. In the case of a large, deep water body, however, water temperatures commonly lag behind the temperature of the overlying air. During the spring and early summer months considerable depths of water are slowly and gradually warmed up by a part of incoming solar energy which would otherwise be available for evaporation. Subsequently, the slow release by the deep water body of the stored heat during the autumn and winter months, means that a supply of heat energy in excess of that received directly from the sun is made available for evaporation at that time of the year. The net result of this heat storage on relative air and water temperature is that water temperatures are lower than air temperatures during the summer, and higher during the winter. Since, according to Dalton's law, evaporation is proportional to the differences between saturation vapour pressure at the temperature of the water surface, and actual vapour pressure of the overlying air, it will be apparent that the highest rates of evaporation from deep water bodies should occur during the winter. Furthermore, at that season, water vapour-laden air will be rapidly lifted away from the underlying water surface as a result of convectional activity, encouraged by the temperature gradient, whereas during the summer, the colder water will tend to cool and stabilize the air immediately above it, and so inhibit the removal of vapour-laden air. Despite the seasonal discrepancies which have been noted above, it is unlikely that the annual evaporation from deep and shallow waters will differ very markedly (Ward, 1967). For shallow lakes the amount of heat storage is negligible. In deep bodies of water, however the heat storage can not be neglected. A portion of the radiation energy received in summer is stored in the water mass and is returned back during the winter. Therefore, for an equal quantity of radiation received, the amount of evaporation will be less in a hot season and more in a cold season. On annual basis, the changes in storage will be negligible for deeper reservoirs. However, the monthly distribution of three total annual evaporation will be markedly affected by this heat storage term. In shallow lakes, the average water temperature for monthly periods do VI not differ greatly from air temperatures and the rate of evaporation is therefore higher during the summer (hot season) than during the winter (cold season). Because of the greater heat storage in deep lakes, the temperature of trie water will lag behind the temperature of the air above. This will reduce the summer evaporation and increase the winter evaporation above the rates on the shallow lakes (Balek et al., 1994). 3) The measured evaporation values at the meteorology station belong to the three months in the summer season. But, as mentioned above, since lake Van is deep, it has a large heat storage. The evaporation over Lake Van occurs throughout the whole year, however, the maximum evaporation occurs during winter. But, the measured evaporation in the meteorology station during three months of the summer season is taken as total annual evaporation. That is, the large evaporation in the remaining 9 months are not considered. Due to the lack of 9 months, the measured evaporation at the meteorology station does not represent the evaporation over Lake Van. Because of that, the best approach to calculate the evaporation over Lake Van is the water balance method (Muslu, 1993). The, continuity equation is expressed as follows: P + I-E-Y-F = AS (2) P = Precipitation over the lake (m3), I = Amount of water inflow to the lake (m3), E = Evaporation over Lake Van (m3), Y = Amount of water outflow from the lake (m3), F = Seepage to the lake or to the ground (m3), AS = Net change in the water level (m3). In using the balance equation above for Lake Van, the following assumptions were made; Since Lake Van is a closed lake, there is no outflow. Therefore the amount of outflow is assumed to be zero in the balance equation. Since determination of the F term is difficult, this term is also assumed to be zero. In this case, the balance equation is rewritten as, E = P+I- AS (3) Hence, E = Evaporation over Lake Van (m3), P = Precipitation over Lake Van (m3), I = The surface runoff from the basin to Lake Van (m3), AS = Net change in the water level (m3). Both the precipitation over Lake Van and the precipitation over its basin is computed by Percentage Weighting Polygon Method (YA) developed by Şen (1994). Data related to the precipitation were obtained from the 23 meteorological station managed by DMt. The total annual discharges of the rivers; Hoşap Suyu, Bendimahi Çayı and Süfrezor Deresi, were taken as the total annual discharge of the three rivers were used in the balance equation. Surface runoff coming to Lake Van causes changes in lake vu levels. Because of this, relationship between precipitation and surface runoff on its basin must be well known. That is, surface runoff coefficient must be computed. In this study, surface runoff coefficient for the Lake Van basin was computed, using several different methods: 1) Firstly, runoff coefficient is the slope of the line which is fitted to scattering diagram of precipitation versus surface runoff (Bayazit, 1991). 2) Secondly, to compute surface runoff coefficient, total input to the Lake Van is devided by long term average precipitation o ver its basin (Kempe, 1978). 3) Finally, the YAKAÇ method, developed by Şen et. all. in 1995. Rivers mentioned above do not represent total surface runoff coming to the Lake Van. In addition to these rivers, there are also three rivers on the Lake Van basin. Moreover records belong to these rivers are not available in present period. Because of these, the runoff coefficients are computed for each river by the YAKAÇ method. Then, by taking average of these runoff coefficients, runoff coefficient for the Lake Van basin is found to have approximately, a value of 0.4. Surface runoff coefficients which are calculated by all these methods are all close to 0.4. Next step, surface runoff coming to the Lake Van is computed again, multiplying surface runoff coefficient by precipitation over its basin, by taking the runoff coefficient as 0.4. In this way, an ettempt is made to represent the surface runoff coming to the Lake Van and its basin more accurately. Besides, surface runoff, the relationship between the precipitation and the flow of the basin is also examined. Evaporation from the lake surface has the highest degree of uncertainty of any of the basin variables; it is indirectly computed rather than measured. The evaporation from the Lake Van was computed in three difference ways using the water balance equation for the 1 973-1 990 period: 1) -Evaporation from the lake surface is computed by multiplying measured evaporation data by 0.7 which is taken as pan coefficient. 2) Evaporation from lake surface is computed by using the hydrological balance equation, assuming as a inflow, the total of discharge of the above mentioned three rivers. 3) Evaporation from lake surface is computed by using hydrological balance equation, but this time multiplying the precipitation over the basin by the runoff coefficient, which is taken as 0.4. Then, these results were compared to the results which was computed as depending on coefficients. It is shown that the calculation of the evaporation from Lake Van by using the pan-coefficient is not convenient. And then, changes in volume of the Lake Van are calculated by means of the parameters for the 1974-1990 period and are compared to observed changes in its volume. It is found that the evaporation from the lake surface has the lowest value in 1987 and 1988. It has been said that the extraterrestrial affects such as the number of sun spots and meteor showers effect the earth's atmosphere and the lakes. Moreover, some of the studies indicate some correlations between hydrometeorological observations and the 1 1-year fluctuations of the number of the sun spots. In this study, it has been shown that there is no relationship between the water levels of Lake Van and the observed monthly numbers of the sun spots. vııı In 1987 and 1988, the level of water increased: In the same years, both the amount of precipitation over Lake Van and over its basin were also increased. As a result of the increase in the precipitation over its basin, an increase in surface runoff coming to Lake Van was observed. As a result of the increase in the precipitation over its basin, an increase in the water level was also observed. In the period of 1975-1986, in which the water level is balanced, the total water mass coming to the Lake Van is also balanced. However, while the total mass coming to the Lake has been increasing since 1987, the evaporation from the Lake has begun to decrease. This decrease in the evaporation had a minimum value in 1988. In 1987 and 1988, because of the increase in precipitation over both Lake Van and over its basin, the total water mass coming to the Lake, is not balanced by the evaporation from the Lake Van.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1996
Keywords: su seviyesi; Van gölü; iklim; water level; Van lake; climate